Field measurement in vegetable crops indicates need for reevaluation of on-farm food loss estimates in North America. (November 2018) - Johnson, Lisa K.; Dunning, Rebecca D.; Gunter, Chris C.; Dara Bloom, J.; Boyette, Michael D.; Creamer, Nancy G.
Abstract: Food loss and waste in the US has been estimated at 40%, a figure that does not include losses at the agricultural level. Consumer food waste is expensive and environmentally damaging as it travels the length of the supply chain and largely ends up in the landfill. Most research and campaigns emphasize the consumer level, which has resulted in the omission of data collection and development of solutions for producers of fruit and vegetable crops. The available estimates of edible produce lost in the field are based on assumptions and estimates, rather than field data. Therefore, this project aimed to measure losses in the field in order to understand if estimates are accurate. Sixty-eight fields of eight vegetable crops were evaluated on nine North Carolina farms during the 2017 production season, using a sampling and scaling method. Combining the unharvested crops of marketable quality and edible but not marketable quality (produce that does not meet appearance quality standards), the average produce volume available after the primary harvest was 5114.59 kg per hectare. Totaling an average of 42% of the marketed yield for these crops, these high figures indicate the need for a reevaluation of the food loss estimates at the agricultural level in the US, and a focus on solutions. Highlights: 68 fields of vegetable crops were evaluated during 2017 using sampling and scaling. Grand mean of fresh produce left unharvested in the field was 5114.59 kg/ha. Available, unutilized produce averaged 42% of North Carolina marketed yields. Research is needed as these estimates exceed current estimates of food loss. Reducing food loss is expected to impact farm sustainability and food supply.